Secular Stagnation: The Long View - Eichengreen, Barry (American Economic Review, 2015)
Four explanations for secular stagnation are distinguished: a rise in global saving, slow population growth that makes investment less attractive, adverse trends in technology and productivity growth, and a decline in the relative price of investment goods. A long view from economic history is most supportive of the last of these four views.